Pt(IV) Prodrugs with Non-Steroidal Anti-inflammatory Drugs in the Axial Position - Spector, Daniil V.; Pavlov, Kirill G.; Akasov, Roman A.; Vaneev, Alexander N.; Erofeev, Alexander S.; Gorelkin, Petr V.; Nikitina, Vita N.; Lopatukhina, Elena V.; Semkina, Alevtina S.; Vlasova, Kseniya Yu; Skvortsov, Dmitrii A.; Roznyatovsky, Vitaly A.; et al. (Journal of medicinal chemistry, 2022)
We report herein the design, synthesis, and biological investigation of a series of novel Pt(IV) prodrugs with non-steroidal anti-inflammatory drugs naproxen, diclofenac, and flurbiprofen, as well as these with stearic acid in the axial position. Six Pt(IV) prodrugs 5–10 were designed, which showed superior antiproliferative activity compared to cisplatin as well as an ability to overcome tumor cell line resistance to cisplatin. By tuning the drug lipophilicity via variation of the axial ligands, the most potent Pt(IV) prodrug 7 was obtained, with an enhanced cellular accumulation of up to 153-fold that of cisplatin and nanomolar cytotoxicity both in 2D and 3D cell cultures. Pt2+ species were detected at different depths of MCF-7 spheroids after incubation with Pt(IV) prodrugs using a Pt-coated carbon nanoelectrode. Cisplatin accumulation in vivo in the murine mammary EMT6 tumor tissue of BALB/c mice after Pt(IV) prodrug injection was proved electrochemically as well. The drug tolerance study on BALB/c mice showed good tolerance of 7 in doses up to 8 mg/kg.